Avaliação da eficácia e segurança clínica de uma formulação neurolítica injetável para uso perineural em equinos - Escodro, Pierre Barnabé (2011)
The control of chronic pain in equines is growing up recent years in function of the highest performance required of the animals in the different sportive modalities and the new look for methodologies of combat to animal maltreatment. It is cited even, the economic potentialities in the economic chain of the equine breeding to stimulation of the development of new technologies and products. In attendance to these rules, the work presented here brings the evaluation of the effectiveness and clinical security of a injectable neurolytic formulation for perineural use in equines. This type of drug is not yet available in Brazilian market. The Injectable Neurolytic Suspension (SNI) was formulated with ethanol, triamcinolone and bupivacaine, aiming at to use to advantage the neurolytic effect of ethanol, with no collateral inflammatory reactions and painful in local injection. The evaluation of chemical stability was carried through the evaluation of the loss of weight of the samples, variation of pH, time of sedimentation after the agitation and development of chromatographic method for identification and simultaneous determination of bupivacaine and triamcinolone. The clinical test was carried through per 180 days in five horses, having approached two aspects: (a)evaluation of the effectiveness of the neurolytic action and pain suppression of the SNI, and (b)the eventual toxicity related to the composition. The lameness was induced in the horses through the development of horseshoes method, carrying later through perineural infiltration of 5 mL of SNI in each branch of the palmar nerves. The evaluation of the SNI toxicity was carried out monitoring of the hepatic, kidney and skeletal muscle functions, measuring the serum levels of alanina aminotransferase (ALT), aspartate aminotransferase (AST), creatinofosfokinase (CK), Gamaglutamiltransferase (GGT), Urea and Creatinine. The SNI presented satisfactory chemical stability in temperatures of 4ºC and 20ºC. The clinical test indicated abolition of podal pain in the horses from 96 hours of infiltration, with effect kept up to 180 days. The SNI did not caused hepatic, kidney and/or skeletal muscle toxicity. All the results lead to a very promissory drug to this specific market in Brazil.